Seven Years of Retention of Severe Mandibular Prognathism Treated With Bimaxillary Surgery: Two Case Reports - Tulin Ufuk Toygar-Memikoglu; Halise Aydemir; Hakan Alpay Karasu; Nejat Bora Sayan (Galenos Yayinevi, 2013)
These case reports describe the surgical treatment of 2 male adult patients with severe mandibular prognathism. For both patients, anterior repositioning of the maxilla by Le Fort I osteotomies with and without impaction and mandibular posterior repositioning by sagittal split ramus osteotomies were performed. The aim of this case report is to identify successfully treated surgical cases maintaining the results throughout the follow-up period of 7 years.